Intranasal Dental Repulsion of a Displaced Cheek Tooth in an Arabian Filly - Alessandro Spadari; Giuditta Saragoni; Federica Meistro; Maria Virginia Ralletti; Francesca Marzari; Riccardo Rinnovati (Animals)
This case report documents an unusual cheek tooth (CT) displacement in a 3-year-old Arabian filly. The horse was referred to the clinic for loss of appetite and right-sided facial deformity. At admission, an oral inspection was performed, followed by a dental radiographic examination. The radiographs showed a very oblique vertical angulation (135°) of the CT 106 compared to the other premolars (107 and 108 CTs) (40°). In consideration of the clinical and radiographic findings, surgical extraction of the 106 CT was indicated. Due to the unique positioning of the displaced tooth, traditional extraction methods such as standing oral extraction or minimally invasive buccotomy were deemed impractical. An innovative intranasal dental repulsion technique was selected to minimize invasiveness while ensuring the possibility of performing a complete oral extraction. The procedure was performed under general anesthesia without requiring skin incisions or a lateral osteotomy of the maxilla. The surgery was successful, with no intra-operative or post-operative complications. This original approach offers a viable alternative for similar cases, reducing the morbidity associated with conventional repulsion techniques.